Samurai cat goes to the movies - Rogers, Mark E. (Mark Earl), 1952- (New York : TOR, 1994)
Japan's most ferocious feline warrior (and his sidekick Kitty, Shiro) take on the glamour of "Hellywood" and tackle such opponents as the Terminationer and others.
"A Tom Doherty Associates book.".
Booklist.
Kirkus Review.
Voice of Youth Advocates (V.O.Y.A.).
Adult
Keywords: Cats -- California -- Los Angeles -- Fiction; Cats -- Fiction; Hollywood (Los Angeles, Calif.) -- Fiction; Hollywood (Los Angeles, Calif.) -- Fiction; Fantastic fiction; Fantastic fiction